(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Modern medical education faces the challenges of digitalization, globalization and rapid technological changes, which requires rethinking the content and methods of teaching fundamental disciplines. One such discipline is biophysics, which provides an interdisciplinary link between physics, biology and clinical practice. The article considers the role of competence approach as a conceptual basis for modernization of teaching of biophysics in medical schools, analyzes international educational models and national reforms in Uzbekistan. Methodological guidelines for the implementation of innovative learning technologies capable of ensuring the formation of professional competences of students are determined. Emphasizes the need to develop adapted pedagogical solutions that integrate active forms of learning and digital tools, on the basis of which the ground is created for the application of modern technologies to optimize the educational process.